Dislocation reconfiguration during creep deformation of an Al-Cu-Li alloy via electropulsing. (10th December 2022) - Zhou, Chang; Zhan, Lihua; Li, He; Liu, Chunhui; Xu, Yongqian; Ma, Bolin; Yang, Youliang; Huang, Minghui
Highlights: Our findings proved another dislocation reconfiguration responsible for the electroplastic behaviour. Synergy of the climb force F c and electron wind force F ew on the reconfiguration of helical dislocations. Athermal component of electropulsing is proven to be more important during the dislocation reconfiguration. Abstract: Creep mechanism was well-known to be mainly dominated by the dislocation sliding and climbing during creep deformation. Here we study the creep deformation of an Al-Cu-Li alloy with the assistance of electropulsing and subsequent microstructural observations. We find that creep strain increased drastically under electropulsing and was almost twelve times as much as that of the non-pulsed sample. Microstructural observations confirmed that dislocation reconfiguration happens via electropulsing, namely helical dislocations being opened rapidly. This opened dislocation structure can possess a much higher mobility than the initial helical dislocation, which mostly responsible for the greatly increased creep strain. Our results revealed a new mechanism accountable for the distinctly electroplastic creep deformation. Graphical Abstract: Image, graphical abstract